Como resolver essa expressão (+13)+(-4)+(-7)+(-2)+(+15)+(+2)+(-16)
Soluções para a tarefa
Respondido por
1
(+13)+(-4)+(-7)+(-2)+(+15)+(+2)+(-16) =
13 - 4 - 7 - 2 + 15 + 2 - 16 = 1
bons estudos ;)
Se tiver dificuldade pode separar a subtração da adição:
(- 4 - 7 - 2 - 16 ) + (13 + 15 + 2)
- 29 + 30 = 1
13 - 4 - 7 - 2 + 15 + 2 - 16 = 1
bons estudos ;)
Se tiver dificuldade pode separar a subtração da adição:
(- 4 - 7 - 2 - 16 ) + (13 + 15 + 2)
- 29 + 30 = 1
caahta:
Respondido
Perguntas interessantes
História,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás